Absence of nystagmus during REM sleep in patients with vestibular neuritis. Issue 3 (1st September 2001) - Eisensehr, I; Noachtar, S; Strupp, M; v Lindeiner, H; Brandt, T; Büttner, U
Abstract : Saccades, including fast phases of nystagmus, disappear during drowsiness and non-rapid eye movement (NREM) sleep, but are present during the alert state and REM sleep. The purpose of this study was to determine whether spontaneous nystagmus is present in patients with vestibular neuritis during REM sleep. Eight patients with spontaneous nystagmus due to vestibular neuritis and eight control patients without any nystagmus underwent at least one night of polysomnography. Fast phases of nystagmus were analyzed. The number of right and left horizontal saccades were counted, first during 3–5 minute samples of the awake state before sleep onset, then during the first REM episode and the last REM episode of nocturnal sleep, and finally during the alert state in the morning after nocturnal sleep. All patients with vestibular neuritis showed significantly more saccades (fast phases) towards the side contralateral to their vestibular lesion in the awake state before and after the polysomnography. This reflects their spontaneous nystagmus. By contrast, during REM sleep the patients with vestibular neuritis showed no preponderance in saccade direction. The eye movement pattern in REM was the same for patients and controls. In conclusion, peripheral vestibular imbalance producing nystagmus in vestibular neuritis in the awake state is not active at the brain stem level during REM sleep.